2014
DOI: 10.1016/j.jtcvs.2014.06.079
|View full text |Cite
|
Sign up to set email alerts
|

The biomarker TP53 divides patients with neoadjuvantly treated esophageal cancer into 2 subgroups with markedly different outcomes. A p53 Research Group study

Abstract: The biomarker TP53 divides esophageal cancer patients into 2 categories with markedly different outcomes: patients with a normal TP53 marker status may experience notable benefits from neoadjuvant chemotherapy with cisplatin/fluorouracil, whereas those with a mutant TP53 marker status appear to be at risk for lack of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Both drugs are thought to depend on normal TP53 . The results of this study supported the hypothesis that TP53 could serve as potential predictive marker for response to neoadjuvant chemotherapy [7]. …”
Section: Introductionsupporting
confidence: 84%
“…Both drugs are thought to depend on normal TP53 . The results of this study supported the hypothesis that TP53 could serve as potential predictive marker for response to neoadjuvant chemotherapy [7]. …”
Section: Introductionsupporting
confidence: 84%
“…For esophageal [4,6] and oropharyngeal cancer [7] and diffuse large B-cell lymphoma (DLBCL) [3], mutp53 was indeed a good predictor of resistance to chemotherapy. Cisplatin and fluorouracil were less efficacious in patients with esophageal and oropharyngeal cancer and the p53 mutations than in those with wild-type p53.…”
Section: The Role Of Mutp53 In Response To Clinical Chemotherapymentioning
confidence: 99%
“…Thus, p53 is a major candidate gene that can serve as a molecular marker in combination with other genes to be able to tailor chemotherapy to the individual patient. Recently, mutant p53 (mutp53) has been identified as a good predictor of chemoresistance in some clinical studies [3,4,5,6,7], and drugs targeting mutp53 have been developed. In this review, we provide an update regarding the mechanisms that underlie mutp53 gain of function (GOF) mutations, summarizing the mechanisms by which mutp53 induces chemoresistance and elucidating the role of mutp53 in clinical chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study showed that EC patients with a normal TP53 status may benefit from nCRT with cisplatin/fluorouracil compared with mutant TP53 status (no immunohistochemical analysis performed). 47 Patients in our study were treated according to the CROSS regimen, consisting of carboplatin þ paclitaxel and radiotherapy. Carboplatin and radiotherapy are likely to act via a p53-controlled pathway, but docetaxel acts differently, and it is not clear if and how it interacts with TP53.…”
Section: Discussionmentioning
confidence: 99%